The effect of 6 weeks of creatine monohydrate supplementation on dynamic rate of force development - Haff, G. G.; Kirksey, K. B.; Stobne, M. H.; Warren, B. J.; Johnson, R. L.; Stone, M.; O'Bryant, H.; Proulx, C. (The Journal of Strength and Conditioning Research, 2000)
The effects of creatine supplementation on force-time curve (FTC) characteristics were investigated in collegiate track athletes. Sixteen male and 20 female athletes were randomly divided into a placebo (P, n = 21) and a creatine (Cr, n = 15) group. Six weeks of supplementation consisted 0.3 g per kilogram of body weight per day of Cr monohydrate or nonnutritive placebo. Subjects were involved in a periodized weight-training program centered on explosive exercises. Pretesting and posttesting consisted of 7-site skinfold analysis, countermovement vertical jump (CMJ), and static vertical jump (SJ). SJ was performed on a 61.0- × 121.9-cm ATMI (Advanced Medical Technologies, Newton, MA) force plate and was analyzed for FTC. No differences were found between the 2 treatments for FTC. The CMJ showed a significant group by time interaction with the Cr group improving at a greater rate than did the P group. Lean body mass (LBM) significantly increased in the Cr group after the treatment period. These results suggest that 6 weeks of Cr supplementation can favorably enhance LBM and CMJ performance in track athletes.